Desarrollo de las habilidades motrices básicas a través de la cultura física y deportes en los niños de 4 años del centro educativo Daniel Rodas Bustamante, ciudad de Loja, 2014 - Guerrero Rodríguez, Iliana de los Ángeles (2015)
Basic motor skills are fundamental to the full development of the human being, since it is through the body and movement as people are related to the environment, this research entitled development of basic motor skills through physical culture and sports in children 4 years of the educational center "Daniel Rhodes Bustamante" city of Loja 2014. Whose problem focuses on the of implementation of the course of physical culture in initial education making it difficult to motor development child, causing high levels of stress and a low physical response. The objective is to whether the subject of physical culture and sports allows the development of basic motor skills. For which we used analytic–synthetic method, Inductivo-Deductivo, Historico-logico, as well as also techniques and instruments as applied to teachers and parents and the test motor which to identify deficiencies in the development of basic motor skills, also used a qualitative approach in collecting information and data analysis with a type of longitudinal study to the duration of the research, made their sometimes experimental pre design since we worked with a group, to which applied you a pre test coupled with the age of the study group, in order to diagnose the level of development of basic motor skills the results, were making an alternative proposal had a duration of 24 weeks of application and at end of the implementation of the proposal proceeded to evaluate the work with a test post. Resulting through the Pearson coefficient ɤ (x, and), there is a correlation between work and engine improvement of group generating a result with positive sign of 0.6. There was 98% credibility. Is for this reason that it is necessary to recommend the implementation plan for physical activities - leisure focused on the game to provide development, stimulation and improvement of motor skills in children in early education into the teaching-learning process.